THE IMPORTANCE OF UTILIZING ADVANCED GRAMMAR AND PUNCTUATION TO IMPROVE LEARNERS’ WRITING (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2024)
Annotation. Learning the grammar of a new language is an essential part of the language learning process. A strong grasp of grammar not only helps in understanding the structure of the language but also allows for deeper and more accurate communication. In addition, using words correctly in writing and applying punctuation marks appropriately are key elements that enhance clarity and meaning. Mastering these aspects is crucial for effective writing, as it enables the writer to express their thoughts clearly and cohesively. Proper punctuation, for instance, helps guide the reader through the text and ensures that the intended meaning is conveyed without ambiguity. These topics are fully explored in the article, which emphasizes the importance of grammar and punctuation in improving writing skills and ensuring proper communication, both in written and spoken forms.